2021
DOI: 10.1111/tmi.13692
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents’ experiences with group antenatal care: Insights from a mixed‐methods study in Senegal

Abstract: ObjectivesGroup antenatal care (G‐ANC) is an innovative model in which antenatal care is delivered to a group of 8–12 women of similar gestational age. Evidence from high‐income countries suggests G‐ANC is particularly effective for women from marginalised populations, including adolescents. The objective of this study was to examine the experiences of Senegalese adolescents engaged in group antenatal care.MethodsThis convergent parallel mixed‐methods study is derived from a larger effectiveness–implementation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Group service provision has also been reported to be favored in other studies, as it promotes information sharing related to health, social interactions, and connections which is bene cial to both young and old women (25).…”
Section: Discussionmentioning
confidence: 99%
“…Group service provision has also been reported to be favored in other studies, as it promotes information sharing related to health, social interactions, and connections which is bene cial to both young and old women (25).…”
Section: Discussionmentioning
confidence: 99%
“…The eligibility criteria for papers to be considered for inclusion in the review are presented in Table 1 . To be included, studies had to report data on women receiving perinatal group care, that is, care within 1000 days of care from the start of the pregnancy 11 , 28 ; the intervention was centering-based perinatal care, 1 or synonym model known as G-ANC, 2 , 3 , 4 , 5 or similar models like Group Based Antenatal Care, 9 Expect With Me, 8 Pregnancy Circles 10 or Connecting Pregnancy 7 ; the control group was standard individual care; and, studies reported a measure of overall satisfaction with care. Group care is provided during antenatal and postnatal periods; therefore, it is important to examine satisfaction during all stages of perinatal care.…”
Section: Methodsmentioning
confidence: 99%
“… 1 In many countries, this model is known as group antenatal care (G-ANC). 2 , 3 , 4 , 5 , 6 There are similar models that share a similar philosophy and derived from the original model, including Connecting Pregnancy, implemented in Canada, 7 Expect With Me, implemented in the United States, 8 Group Based Antenatal Care, implemented in Denmark and Sweden, 9 and Pregnancy Circles implemented in the United Kingdom. 10 …”
Section: Introductionmentioning
confidence: 99%